Analisa Pengaruh Bentuk Impingement Plate Terhadap Perpindahan Panas Pada Zona Desuperheating High Pressure Heater - Arrad Ghani Safitra (Politeknik Negeri Padang, 2021)
High Pressure Heater (HPH) are tools that used to improve the efficiency of boiler. HPH utilizes hot steam from turbine extraction as heating medium before entering into the economizer in boiler. In the industry, High Pressure Heater is one of the tools that includes a heat exchanger. To prevent from several problems, some of the industries applying a plate that called impingement plate. This plate placed on the shell side Steam inlet of High Pressure Heater with the function to protect the tube facing the directly the shell side input flow. To determine the effect of adding impingement plates on heat transfer that occurs in the desuperheating zone, a simulation was performed using CFD software with variations of conventional flat plates, 4 plates, and inclined plates. From the simulation results using CFD software it is known that after the addition of the impingement plate, the largest heat transfer value in the desuperheating zone is found in the inclined plate geometry followed by the 4 plate geometry and conventional flat plate, with a q value of 9.54 MW; 7.93 MW; and 4.16 MW, respectively. Then for the inclined plate geometry pressure drop value has a small pressure drop plaing value, which is equal to 30.04 kPa.